A Unified Linear Self-Regulating Method for Active/Reactive Sustainable Energy Management System in Fuel-Cell Connected Utility Network - Kamrul Hasan; Muhammad Murtadha Othman; Sheikh Tanzim Meraj; Masoud Ahmadipour; M. S. Hossain Lipu; Mohsen Gitizadeh (IEEE Access, 2023)
In fuel-cell-connected utility networks, electrical loads attached to the power network often generate reactive power, which hinders the utility from normal functioning and reduces the system power factor. This condition results in wasted energy, increase demand for electricity, system overload, and higher utility costs for customers. Besides, a power system’s poor power factor is often caused by a large distorted reactive power element because of the widespread use of non-linear loads. Moreover, power outages were brought on by voltage dips resulting from reactive power. In a fuel cell-based network, traditional utilities often use classical filters that are unable to remove harmonic properties, and incapable of compensating for the reactive power. Moreover, power outage compensation is overlooked in most fuel cell-based energy systems. To address this problem, the proposed article provides a novel unified linear self-regulating (LSR) active/reactive sustainable energy management system (SEM) that can adjust the power factor by compensating for power outages and reactive power, and precisely removing harmonics from the electricity network. As a result, the suggested mechanism may avoid power losses and allow users to save money on their power costs. Furthermore, notwithstanding grid availability, the critical loads receive an uninterrupted power supply due to the automatic transition circuit implemented in the SEM. The suggested system’s performance is evaluated under various load circumstances and the findings have shown that the suggested SEM can successfully decrease harmonics from the network while also keeping the power factor of the electricity network near unity.